Investigasi Motivasi dan Strategi Manajemen Laba pada Perusahaan Publik di Indonesia - Achmad, Komarudin; Subekti, Imam; Atmini, Sari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
This study investigates the existence of earnings management motivations and strategies. Based on ordinary least square regression, this study indicates that debt covenant and political cost motivations affect earnings management. However, bonus plan motivation and accounting method choice strategy do not affect earnings management. Investigation on earnings management practices explains that bonus plan motivation affect income increasing, not income decreasing. This study finds that the managers of public firms in Indonesia do not use accounting method choices as earnings management strategy. Some of them choose to use a little of accruals accounting flexibility and prefer both GAAP violations and intercompany transactions strategies. This study identifies that the motivations of debt covenant, political cost and owners’ wealth as well as the strategy of accruals accounting flexibility are earnings management practices with global value. Otherwise, earnings management practices with local value consist of motivation caused by both debt restructuring and going concern constraint and strategy through GAAP violations and intercompany transactions. Key Words: Earnings management, Motivation, Bonus plan, Debtcovenant, Political cost, Owners’ wealth, Debt restructuring, Going concern, Strategy, Accounting method choice, Accruals accounting flexibility, GAAP violations, Inter company transactions, Global value, Local value